Isokinetic strength differences between elite senior and youth female soccer players identifies training requirements. (September 2019) - Eustace, Steven James; Page, Richard Michael; Greig, Matt
Abstract: Objectives: To compare traditional and angle-specific isokinetic strength of eccentric knee flexors and concentric knee extensors in female senior professional and youth soccer players. Design: Cross-sectional study design. Setting: University's Laboratory. Participants: A total of 34 players (17 seniors [age 25.31 ± 4.51 years; height 167.89 ± 7.04 cm; mass 63.12 ± 7.79 kg] and 17 youths [16.91 ± 1.16 years; height 165.92 ± 4.42 cm; mass 60.07 ± 4.48 kg]) from the Women's Super League 1 completed strength assessments at 180, 270 and 60°∙s −1 . Main outcome measures: Peak torque (PT), dynamic control ratio (DCR), angle of peak torque (APT), functional range (FR), angle-specific torque (AST) and angle-specific DCR (DCRAST ) were compared between age groups. Results: The PT ( P  = 0.016) AST ( P  = 0.041) were significantly higher in seniors compared to youths; however APT ( P  = 0.141), DCR ( P  = 0.524) FR ( P  = 0.821) and DCRAST ( P  = 0.053) were not significant between playing age. Conclusion: The use of absolute and angle-specific strength measures were able to distinguish between female playing ages, whereas DCR and DCRAST was unable to identify differences. The PT and AST metrics may be the most useful metrics to help identify and inform training needs, particularly in youths. Highlights: Thigh musculature strength of female soccer players influenced by playing age. No differences in strength ratios across female soccer playing age. These metrics can inform training and better prepare youths for senior match-play.